Aversion to a High Salt Taste is Disturbed in Patients With CKD - Natsuko Okuno-Ozeki; Yusuke Kohama; Hiromu Taguchi; Yuka Kawate; Minato Umehara; Atsushi Minamida; Hiroko Yamauchi-Sawada; Yasuto Sunahara; Yayoi Matoba; Itaru Nakamura; Kunihiro Nakai; Tomohiro Nakata; et al. (Kidney International Reports)
Introduction: A reduced salt intake is a vital lifestyle modification in the management of hypertension. Initiatives aimed at decreasing the intake of salt are based on the preference by humans for a salt taste. Salt intake behavior appears to be affected by the balance between attraction to a low salt taste and aversion to a high salt taste. However, aversion to a high salt taste has not yet been quantitively investigated in both healthy individuals and patients with chronic kidney disease (CKD). Methods: Assessments of gustatory and aversion thresholds for salt, bitter, sour, and sweet tastes were performed using a stimulant-impregnated test strip in healthy subjects and patients with CKD. Results: In a pilot taste test of 125 healthy subjects, the number of participants with an aversive reaction increased at higher salt concentrations. The threshold for normal taste perception was arbitrarily defined as 10% NaCl, with 47.2% of healthy subjects displaying an aversive reaction. In taste tests performed by 70 patients with CKD, 10% were unable to recognize a salt taste, even at the highest concentration (20% NaCl), suggesting a significant impairment in taste perception in patients with CKD. Only 15.7% of patients with CKD exhibited a normal aversion to NaCl, whereas 78.6% showed the complete loss of aversion to salt. Conclusion: The present results confirmed the anticipated aversive response to a high salt taste in humans and demonstrated its impairment in patients with CKD, implying that patients with CKD have reduced resistance to a high salt intake.